Lower RXRA and TFRC expression despite higher mineral and vitamin intake in diabetic pregnant women with pregnancy-specific urinary incontinence - Sarah Maria Barneze Costa; Raghavendra Lakshmana Shetty Hallur; Matheus Naia Fioretto; João Paulo de Castro Marcondes; Igor de Carvalho Deprá; Camila Renata Corrêa; Danielle Cristina Honorio França; David Rafael Abreu Reyes; Sérgio Luis Felisbino; Angélica Mércia Pascon Barbosa; Marilza Cunha Vieira Rudge; M.V.C. Rudge; et al. (Clinical Nutrition Open Science)
Summary: Background: Gestational diabetes mellitus (GDM) and pregnancy-specific urinary incontinence (PSUI) pose significant health challenges for pregnant women, but their metabolic and molecular underpinnings remain poorly understood. Methods: In this cross-sectional study, 1,105 participants from the DIAMATER cohort were categorized based on GDM and PSUI status. Dietary intake of iron, magnesium, zinc, and vitamins A and D was assessed through dietary recalls, while serum levels, gene expression (MTF1, RXRA, TFRC, TRPM6), and protein expression were analyzed using standard techniques. Oxidative stress markers were also measured. Results: GDM-PSUI participants exhibited lower RXRA and TFRC gene expression and decreased TFRC protein levels despite higher intake of magnesium, zinc, and vitamin D compared to GDM controls without PSUI. Serum mineral levels and oxidative stress markers did not differ significantly between groups. Conclusions: Lower RXRA and TFRC expression in GDM-PSUI women, despite increased mineral and vitamin intake, suggests potential molecular targets for interventions aimed at improving management strategies in this population.